Clinical and Psychological Factors Affecting Distress Among Chronic Warfarin Patients with Uncontrolled International Normalized Ratio - Findings and Implications - Muhammad Shahid Iqbal (Asian Journal of Pharmaceutics (AJP), 2024)
Aim: This study aimed to evaluate the clinical and psychological factors of distress among patients on warfarin therapy with uncontrolled International Normalized Ratio (INR) in Pakistan. Materials and Methods: This study used a convenience sampling method to achieve the target size. Perceived distress was measured using a short version of the Cohen Perceived Stress Scale 10. The responses were recorded and statistical analysis was conducted. Results and Discussion: Among the participants, a maximum of the participants were male (n = 280, 68.5%) compared to the females (n = 129, 31.5%). A maximum of the participants were in the above 65 years category. Among all the participants, 347 patients showed the presence of low distress and 62 showed the presence of high distress. This result indicates that there is a positive correlation between the age (P = 0.005) and duration of warfarin (P = 0.011) with distress in included patients. Associated comorbidities and history of hospitalization showed no association with distress in the study population. Conclusion: This study reported that warfarin patients in Pakistan experienced a lower level of distress despite their uncontrolled INR. However, few of the factors, such as age and duration of warfarin, were shown to be associated with the higher level of distress in the study participants.